1996
DOI: 10.1007/s002560050154
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in coccidioidal arthritis

Abstract: MRI findings in coccidiodal arthritis are described. Enhancement of thickened synovium and erosions was seen after intravenous gadopentetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 0 publications
2
19
0
1
Order By: Relevance
“…However, synovial culture is recommended to distinguish coccidioidal from tuberculous synovitis (1). MR imaging reveals findings, although typically with less synovial proliferation, similar to those in the case presented here (5). The hypertrophied synovium enhances after intravenous administration of gadolinium-based contrast material (3,5).…”
Section: Volume 224 ⅐ Numbersupporting
confidence: 67%
See 1 more Smart Citation
“…However, synovial culture is recommended to distinguish coccidioidal from tuberculous synovitis (1). MR imaging reveals findings, although typically with less synovial proliferation, similar to those in the case presented here (5). The hypertrophied synovium enhances after intravenous administration of gadolinium-based contrast material (3,5).…”
Section: Volume 224 ⅐ Numbersupporting
confidence: 67%
“…MR imaging reveals findings, although typically with less synovial proliferation, similar to those in the case presented here (5). The hypertrophied synovium enhances after intravenous administration of gadolinium-based contrast material (3,5). Gadolinium enhancement can also assist in distinguishing enhancing synovium from nonenhancing joint fluid, regardless of the cause of the synovitis (3,12,13).…”
Section: Volume 224 ⅐ Numbersupporting
confidence: 64%
“…In one study, 7 there were 13 musculoskeletal cases of a total of 330 cases reviewed (approximately 4%). Other collections of orthopedic cases, 6,11,12 including a literature review, 7 do not indicate a denominator. In one recent review of 223 primary infections confirmed by elevated complement fixation titers, 50 were extrapulmonary and 28 of those (13% of the total and 56% of the systemic cases) were musculoskeletal.…”
Section: Discussionmentioning
confidence: 98%
“…Infections of virtually all joints have been described. Infections of the knee, elbow, wrist, and ankle are commonly seen, with the knee most frequently involved [51][52][53]. Dissemination similarly has been described in almost every bone.…”
Section: Disseminated Diseasementioning
confidence: 91%